Legal Politics of Regional Quarantine during the Covid-19 Pandemic with the Approach to Implementing Community Activities Restrictions (PPKM) Level 1-4 - Mutia Evi Kristhy; Kiki Kristanto; Edy Siswanto; Ahmad Budi Martono; Ronny Marthius Nababan (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Politics of regional quarantine law with PPKM approach based on Level 1- 4 as an effort by the Government to suppress the increase in positive cases of the Coronavirus (Covid-19). The policy is decided, of course, by considering health, economic aspects, and social dynamics. Determine the status of the district/city level of the pandemic situation. It is based on indicators regarding the adjustment of public health efforts and social efforts in dealing with the pandemic, which was adapted from the recommendations of the World Health Organization (WHO).